Biodiesel Fuel Production By Methanolysis Of Fish Oil Derived From The Discarded Parts Of Fish Catalyzed By Carica Papaya Lipase - P. Pinyaphong; P. Sriburi; S. Phutrakul (Zenodo, 2011)
In this paper, naturally immobilized lipase, Carica papaya lipase, catalyzed biodiesel production from fish oil was studied. The refined fish oil, extracted from the discarded parts of fish, was used as a starting material for biodiesel production. The effects of molar ratio of oil: methanol, lipase dosage, initial water activity of lipase, temperature and solvent were investigated. It was found that Carica papaya lipase was suitable for methanolysis of fish oil to produce methyl ester. The maximum yield of methyl ester could reach up to 83% with the optimal reaction conditions: oil: methanol molar ratio of 1: 4, 20% (based on oil) of lipase, initial water activity of lipase at 0.23 and 20% (based on oil) of tert-butanol at 40oC after 18 h of reaction time. There was negligible loss in lipase activity even after repeated use for 30 cycles. : {"references": ["K. Annapurna, M. Paramita, G. K. Vijay and B. Rintu, \"Enzymatic\ntransesterification of Jatropha oil,\" Biotech& Biofuels, vol. 2, no page,\n2009.", "N. Kaili, X. Feng, W. Fang and T. Tianwei, \"Lipase catalyzed\nmethanolysis to produce biodiesel: optimization of biodiesel\nproduction,\" J. Mol. Catal. B: Enzym. Vol 43, 142-147, 2006.", "W. Hong, Z. Min-hua, L. Qian and W. Hua-chang, \"Enzymatic\nconversion of waste oil to biodiesel in a solvent-free system,\" Prepr.\nPap. Am. Chem. Soc., Div. Fuel Chem. Vol. 48, 533-534, 2003.", "R. Alcantara, J. Amores, L. Canoira, E. Fidalgo, M. J. Franco and A.\nNavarro, \"Catalytic production of biodiesel from soy-bean oil, used\nfrying oil and tallow,\" Biomass & Bioenergy. Vol 18, 515-527, 2000.", "A. Robles-Medina, P. A. Gonzalez-Moreno, L. Esteban-R Cerdan and E.\nMolina-Grima, \"Biocatalysis: Towards ever greener biodiesel\nproduction,\" Biotechnology Advances., vol. 27, pp. 398-408, 2009.", "L. Lilin, D. Wei, L. Dehua, W. Li and L. Zebo, \"Lipase-catalyzed\ntransesterification of rapeseed oils for biodiesel production with a novel\norganic solvent as the reaction medium,\" J. Mol. Catal. B: Enzym., vol.\n43, 58-62, 2006.", "G. Steinke, R. Kirchhoff and K.D. Mukherjee, \"Lipase-catalyzed\nalcoholysis of crambe oil and camelina oil for the preparation of longchain\nesters,\" J. Am. Oil Chem. Soc., vol. 69, 166-169, 2000.", "Y. Watanabe, Y. Shimada, A. Sugihara, H. Noda, H. Fukuda and Y.\nTominaga, \"Continuous production of biodiesel fuel from vegetable oil\nusing immobilized Candida antarctica lipase,\" J. Am. Oil Chem. Soc.,\nvol. 77, 355-360, 2000.", "W. Du, W. Li, T. Sun, X. Chen and D. Liu, \"Perspectives for\nbiotechnological production of biodiesel and impacts,\" Appl Microbiol\nBiotechnol, vol. 79, 331-337, 2008.\n[10] Y. Shimada, Y. Watanabe, A. Sugihara and Y. Tominaga, \"Enzymatic\nalcoholysis for biodiesel fuel production and application of the reaction\nto oil processing,\" J. Mol. Catal. B: Enzym., vol. 17, 133-142, 2002.\n[11] O. Kose, M. Tuter and H. A. Aksoy, \"Immobilized Candida Antarctica\nlipase-catalyzed alcoholysis of cotton seed oil in a solvent-free\nmedium,\" Bioresour. Technol., vol. 83, 125-129, 2002.\n[12] P. Villeneuve, A. Skarbek, M. Pina, J. Graille and T. A. Foglia,\n\"Catalytic behavior of Carica papaya latex in transesterification\nreactions,\" Biotechnol. Tech., vol. 11, 637-639, 1997.\n[13] M. Kaieda, T. Samukawa, T. Matsumoto, K. Ban, A. Kondo, Y.\nShimada, H. Noda, F. Nomoto, K. Ohtsuka, E. Izumoto and H. Fukuda,\n\"Biodiesel fuel production from plant oil catalyzed by Rhizopus oryzae\nlipase in a water containing system without an organic solvent,\" J.\nBiosci. Bioeng., vol. 88, 627-631, 1999.\n[14] K. Ban, M. Kaieda, T. Matsumoto, A. Kondo and H. Fukuda, \"Whole\ncell biocatalysts for biodiesel fuel production utilizing Rhizopus oryzae\ncells immobilized within biomass support particles,\" Biochem. Eng. J.,\nvol. 8, 39-43, 2001.\n[15] T. A. Foglia and P. Villeneuve, \"Carica papaya latex-catalyzed synthesis\nof structured triacylglycerol,\" J. Am. Oil Chem. Soc., vol. 74, 1447-\n1450, 1997.\n[16] [16] P. Angkanurukpun, P. Sriburi and P. Kanasawud, \"Improvement of\nCarica papaya lipase for methanolysis of triolein,\" Chiang Mai J. Sci.,\nvol. 33, 217-222, 2006.\n[17] L. Cherng-Yuan and L. Rong-Ji, \"Fuel properties of biodiesel produced\nfrom the crude fish oil from the soapstock of marine fish,\" Fuel\nProcessing Technology., 130-136, 2008.\n[18] D. Y. Kwon and J. S. Rhee, \"A simple and rapid colorimetric method for\ndetermination of free fatty acids for lipase assay,\" J. Am. Oil Chem.\nSoc., vol. 63, 89-92, 1986.\n[19] A. S. Ramadhas, S. Jayaraj and C. Muraleedharan, \"Biodiesel production\nfrom high FFA rubber seed oil,\" Fuel., Vol. 84, 335-340, 2005.\n[20] M. Canakci and J. G. Van, \"Biodiesel production from oils and fats with\nhigh free fatty acids,\" Transactions of the ASAE., vol. 44, 1429-1436,\n2001b.\n[21] M. Canakci and J. G. Van, \"A pilot plant to produce biodiesel from high\nfree fatty acid feedstocks,\" ASAE, 2001a.\n[22] K. Krisnangkura, T. Yimsuwan and R. Pairintra, \"An empirical approach\nin predicting biodiesel viscosity at various temperature,\" Fuel., vol. 85,\n107-113, 2006.\n[23] L. A. Nelson, T. A. Foglia and W. N. Marmer, \"Lipase catalyzed\nproduction of biodiesel,\" J. Am Oil Chem Soc., vol. 73, 1191-1195,\n1996.\n[24] V. Dossat, D. Combes and A. Marty, \"Continuous enzymatic\ntransesterification of high oleic sunflower oil in a packed bed reactor:\ninfluence of the glycerol production,\" Enzyme Microb Technol., vol. 25,\n194-200, 1999.\n[25] L. Jike, N. Kaili, X. Feng, W. Fang and T. Tianwei, \"Enzymatic\nsynthesis of fatty acid methyl esters from lard with immobilized Candida\nsp. 99-125,\" Process Biochemistry., vol. 42, 1367-1370, 2007."]}